Development of E-Modules Building a Civilized Society as Learning Media for IPAS Class IV in Elementary School - Dinda Meyshevicha Sundeyani; Erik Aditia Ismaya; F. Shoufika Hilyana (MIMBAR PGSD Undiksha, 2026)
The limited availability of interactive learning media based on local wisdom that integrates civilized values remains a challenge in science and environmental studies (IPAS) learning at the elementary school level. This study aims to develop and analyze the feasibility of an e-module entitled “Building a Civilized Society” as a learning medium for elementary school students. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects involved elementary school students who participated in both limited and large-scale trials. Data were collected through observation, interviews, questionnaires, and documentation, involving material experts, media experts, teachers, and students as respondents. The data were analyzed using qualitative and quantitative descriptive methods to evaluate the feasibility of the developed product. The findings indicate that the e-module demonstrates a high level of feasibility based on expert validation and receives positive responses from both teachers and students. Furthermore, the e-module is effective in enhancing students’ understanding and engagement in the learning process. Therefore, this local wisdom-based e-module has implications as an innovative, contextual, and meaningful digital learning medium that supports effective learning.